Ca Mammae Disease in Andi Makkasau Hospital, Parepare City - M, Ismayanti; Majid, Makhrajani; Putri Rusman, Ayu Dwi (Universitas Muhammadiyah Kalimantan Timur, 2023)
Breast cancer is a neoplastic disease originating from the parenchyma . Indonesia is one of the countries in Asia with the highest incidence of breast cancer with a total of 348,809 cases. The purpose of this study was to determine the factors that can influence the occurrence of breast cancer at Andi Makkasau Hospital, Parepare City. This type of research is observational with a case control approach. The population in this study was the entire population diagnosed with ca mammae at Andi Makkasau Hospital, Parepare City. the sample in this study was 48 respondents with 24 cases and 24 controls, with the sampling technique using total sampling. Data is processed using SPSS. The results of the chi square test for age have a value of p = 0.020 <α 0.05 and OR = 4.048, obesity has a value of p = 1.000 > α 0.05 with a value of OR = 1.000, history of breastfeeding has a value of p = 0.771 with a value of OR = 0.771, family history has a value of p = 0.004 < α 0.05 with a value of OR = 13.800, use of hormonal birth control has a value of p = 0.020 < α 0.05 with a value of OR = 4.048, menstrual history has a value of p = 0.009 < α 0.05 with a value of OR=5,000. It can be concluded that the factors of age, family history, history of using hormonal birth control and menstrual history have a significant effect on the incidence of ca mammae, while obesity and history of breastfeeding have no effect but have a risk of ca mammae events at Andi Makkasau Hospital, Parepare City. It is recommended to maintain a healthy lifestyle and routinely carry out health checks at health workers.